Hola, granja! = Hello, farm! - Frost, Maddie; Workman Publishing Company (New York, NY : Workman Publishing Co., Inc., 2020)
Extends a greeting to farm animals, including horses, cows, and sheep.
Cover title.
Spanish and English.
Keywords: Domestic animals -- Juvenile literature; Spanish language materials -- Bilingual; picture books; Picture books; Juvenile works; Picture books; Livres d'images.